SCIENTIFIC ARTICLE WRITING ASSISTANCE FOR JOURNALS THROUGH THE DISTANCE LEARNING TECHNOLOGY SYSTEM IN COVID-19 PANDEMIC PERIOD FOR TEACHERS OF SMK ACEH TIMUR - Hanafiah Hanafiah; Adi Bejo Suwardi; Asnawi Asnawi; Joko Hariadi (Global Science Society, 2021)
This service aims to provide assistance and guidance for vocational school teachers in East Aceh Regency to write scientific articles in journals through a distance learning system. Assistance in writing scientific articles is important for teachers in East Aceh considering that it is an obligation for teachers to advance in rank or career class. This mentoring is carried out with an online concept through a distance learning system. Mentoring is conceptualized in three stages, namely planning, implementation and evaluation. The target and output to be achieved in this service is to increase the ability of teachers to write scientific articles for journals and to produce outputs in the form of articles published in ISSN journals.